Integrating mental health into primary care: evaluation of the Health Action for Psychiatric Problems In Nigeria including Epilepsy and SubstanceS (HAPPINESS) pilot project - Casey Chu; Nichole Roxas; Chinyere M. Aguocha; Emeka Nwefoh; Katie Wang; Charles Dike; Theddeus Iheanacho (BMC, 2022)
Abstract Background The Health Action for Psychiatric Problems In Nigeria including Epilepsy and SubstanceS (HAPPINESS) project trains non-specialist and primary health care workers in Imo State, Nigeria. This project adapted the World Health Organization's Mental Health Gap Action Programme-Intervention Guide (mhGAP-IG), emphasizing stigma reduction among trainees. This convergent mixed-methods proof-of-concept study evaluates the HAPPINESS pilot project mhGAP-IG training's impact on mental illness stigma among trainees and barriers, facilitators, and opportunities to consider for project improvement. Methods Trainees (n = 13) completed a 43-item questionnaire before and after their 5-day training to assess perceptions of mental disorders and attitudes towards people with mental illness. These responses were analyzed using paired-sample t-tests for four subscales of the questionnaire: acceptance of socializing with people with mental illness, normalizing activities and relationships with people with mental illness, supernatural causation of mental illness, and endorsement of a biopsychosocial approach to mental illness. Semi-structured key informant interviews (n = 11) with trainees, trainers, and local health officials who participated in or supported the HAPPINESS project were thematically analyzed to understand their experiences and perspectives of the project's barriers, facilitators, and opportunities. Results Trainees showed significant improvements on socializing, normalizing, and supernatural causation subscales of the stigma questionnaire (p < 0.05). No significant effect was seen on the biopsychosocial subscale; however, evidence of biopsychosocial beliefs was found in interview responses. Key informant interviews revealed that the HAPPINESS project enhanced trainees' diagnostic and treatment abilities, mental health awareness, and empathy towards patients. Misinformation, stigma, inadequate funding, and lack of road access to clinics were identified as barriers to mental health care integration into general care in Imo State. Respondents also suggested ways that the HAPPINESS project could be improved and expanded in the future. Conclusions This study adds to the limited evidence on the implementation of mhGAP-IG in Nigeria. Using mixed methods, it evaluates how mhGAP-IG can impact perceptions and knowledge of stigma among primary care trainees. It also highlights barriers, facilitators, and opportunities to consider for project growth. Future efforts should focus on clinical support, supervision, health outcomes, as well as scaling up and assessing the cost-effectiveness of the HAPPINESS project intervention.